Staphylococcus aureus dry-surface biofilms are more resistant to heat treatment than traditional hydrated biofilms. Issue 2 (February 2018) - Almatroudi, A.; Tahir, S.; Hu, H.; Chowdhury, D.; Gosbell, I.B.; Jensen, S.O.; Whiteley, G.S.; Deva, A.K.; Glasbey, T.; Vickery, K.
Summary: Background: The importance of biofilms to clinical practice is being increasingly realized. Biofilm tolerance to antibiotics is well described but limited work has been conducted on the efficacy of heat disinfection and sterilization against biofilms. Aim: To test the susceptibility of planktonic, hydrated biofilm and dry-surface biofilm forms of Staphylococcus aureus, to dry-heat and wet-heat treatments. Methods: S. aureus was grown as both hydrated biofilm and dry-surface biofilm in the CDC biofilm generator. Biofilm was subjected to a range of temperatures in a hot-air oven (dry heat), water bath or autoclave (wet heat). Findings: Dry-surface biofilms remained culture positive even when treated with the harshest dry-heat condition of 100°C for 60 min. Following autoclaving samples were culture negative but 62–74% of bacteria in dry-surface biofilms remained alive as demonstrated by live/dead staining and confocal microscopy. Dry-surface biofilms subjected to autoclaving at 121°C for up to 30 min recovered and released planktonic cells. Recovery did not occur following autoclaving for longer or at 134°C, at least during the time-period tested. Hydrated biofilm recovered following dry-heat treatment up to 100°C for 10 min but failed to recover following autoclaving despite the presence of 43–60% live cells as demonstrated by live/dead staining. Conclusion: S. aureus dry-surface biofilms are less susceptible to killing by dry heat and steam autoclaving than hydrated biofilms, which are less susceptible to heat treatment than planktonic suspensions.